Effect of Insecticide and Pesticide on the Growth and Population of Fish - Mritunjay Kumar,; Prof. (Dr.) Faiyaz Ahmad, (International Journal of Scientific Research in Science and Technology, 2025)
Aquatic ecosystems are increasingly threatened by agricultural runoff containing insecticides and pesticides. These chemicals, while beneficial for crop protection, often enter water bodies through surface runoff, infiltration, and aerial drift, leading to adverse effects on non-target aquatic species, especially fish. This paper reviews the impact of various classes of pesticides and insecticides on fish physiology, reproduction, growth rate, and population dynamics. Through an analysis of experimental studies and field observations, the paper highlights both sub-lethal and lethal effects, including oxidative stress, bioaccumulation, endocrine disruption, and behavioral changes. It concludes with a call for stricter regulatory controls and sustainable agricultural practices to minimize aquatic toxicity.
Keywords: Fish; Insecticide; Pesticide